2018
DOI: 10.1016/j.medengphy.2018.07.015
|View full text |Cite
|
Sign up to set email alerts
|

A mixed linear modelling characterisation of gender and speed related changes in spatiotemporal and kinematic characteristics of gait across a wide speed range in healthy adults

Abstract: In exploring the relationship between the kinematics of gait and speed of progression individual variation in patterns and gender differences have not always been adequately taken into account. In the current study mixed linear modelling was used to isolate changes with speed from those associated with individual variation and gender. Three-dimensional motion analysis of 20 participants (10M/10F, 25.7 ± 5.1 years) walking at a wide range of speeds (normalised speeds 0.10-0.55 ∼0.41-2.26 m/s) was recorded (775 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 24 publications
2
14
0
Order By: Relevance
“…As indicated in the introduction women exhibit greater pelvis tilt [11,12] and greater range of motion in the coronal plane while walking compared to men [12]. In current study the greater pelvic tilt for women observed in gait is in accordance with the literature [11,12] and occurs during gait perturbation as well. However, greater pelvic mobility in the coronal plane for gait was not observed in this research.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…As indicated in the introduction women exhibit greater pelvis tilt [11,12] and greater range of motion in the coronal plane while walking compared to men [12]. In current study the greater pelvic tilt for women observed in gait is in accordance with the literature [11,12] and occurs during gait perturbation as well. However, greater pelvic mobility in the coronal plane for gait was not observed in this research.…”
Section: Discussionsupporting
confidence: 90%
“…Pelvis kinematics and the differences between the sexes while executing different movement patterns were the subject of many studies and it was found that women exhibit greater pelvis tilt [11,12] and greater range of motion in the coronal plane while walking compared to men [12].…”
Section: Introductionmentioning
confidence: 99%
“…Pelvic and lower extremity alignment differ between healthy males and females in static positions, 36 and sex differences have been reported during gait for healthy individuals. 6,[18][19][20][21]37 All participants in the present study demonstrated faster walking speeds than previously published cohorts, 38 which may contribute to the lack of sex-dependent sagittal plane gait mechanics in our healthy cohort. following surgery; thus, serial, longitudinal gait assessments will be important for futures studies.…”
Section: Hipmentioning
confidence: 40%
“…14 Sex-specific differences for patient-reported outcomes have been identified, [15][16][17] but the effect of sex on movement impairments has only recently been examined. While sex differences are apparent in gait mechanics of healthy populations, [18][19][20][21] these may be exacerbated in patients with FAIS. 6,8 A cross-sectional study of 21 participants with FAIS compared with 41 healthy comparisons (HCs) found distinct pelvic-femoral kinematics of participants with FAIS that were also sex-dependent.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation